Tumor and microenvironmental mechanisms of resistance to immunomodulatory drugs in multiple myeloma - Chen, Lucia Y.; Gooding, Sarah (Frontiers in Oncology, 2022)
Resistance to immunomodulatory drugs (IMiDs®) is a major cause of treatment failure, disease relapse and ultimately poorer outcomes in multiple myeloma (MM). In order to optimally deploy IMiDs and their newer derivates CRBN E3 ligase modulators (CELMoDs®) into future myeloma therapeutic regimens, it is imperative to understand the mechanisms behind the inevitable emergence of IMiD resistance. IMiDs bind and modulate Cereblon (CRBN), the substrate receptor of the CUL4CRBN E3 ubiquitin ligase, to target novel substrate proteins for ubiquitination and degradation. Most important of these are IKZF1 and IKZF3, key MM survival transcription factors which sustain the expression of myeloma oncogenes IRF4 and MYC. IMiDs directly target MM cell proliferation, but also stimulate T/NK cell activation by their CRBN-mediated effects, and therefore enhance anti-MM immunity. Thus, their benefits in myeloma are directed against tumour and immune microenvironment – and in considering the mechanisms by which IMiD resistance emerges, both these effects must be appraised. CRBN-dependent mechanisms of IMiD resistance, including CRBN genetic aberrations, CRBN protein loss and CRBN-substrate binding defects, are beginning to be understood. However, only a proportion of IMiD-resistant cases are related to CRBN and therefore additional mechanisms, which are currently less well described, need to be sought. These include resistance within the immune microenvironment. Here we review the existing evidence on both tumour and immune microenvironment mechanisms of resistance to IMiDs, pose important questions for future study, and consider how knowledge regarding resistance mechanism may be utilised to guide treatment decision making in the clinic.